Efektifitas Self Manajemen Terhadap Stres Dalam Pembelajaran Daring Era Pandemi Covid – 19 Pada Mahasiswa - Nunik Purwanti; Andikawati Fitriasari (STIKES Karya Husada Kediri, 2022)
Self-management is often used to reduce stress, but application to students who experience stress during the pandemic in dealing with changes in the learning system from face-to-face to online has not been carried out. The purpose of the study was to analyze the effect of self-management on reducing stress in online learning during the Covid 19 Pandemic Era for Nursing Students. This research design uses cross sectional. The population in this study were all students of D3 Nursing Study Program in Semester 5. The sampling technique used was simple random sampling. The number of samples used was 60 students. The independent variable is self-management, the dependent variable is stress. This data collection was done by using a questionnaire. Stress levels were measured using the Depression Anxiety Stress Scale 42 (DASS 42). The Psychometric Properties of the Depression Anxiety Stress Scale 42 (DASS 42) consists of 42 statement items where a score of 0-7 is normal, a score of 15-18 is mild, a score of 19-25 is moderate, a score of 26-33 is severe, a score of 34 is very severe. Data analysis was carried out using the Wilcoxon test with a significance value of = 0.05. The results of the Wilcoxon Sign Rank test = 0.001 (0.001 < 0.05) showed that there was an effect of self-management on reducing stress in nursing students. In general, this study proves that self-management is effective in reducing stress. The use of self-management should be applied to other respondents who experience stress